Parenting stress and child behaviour problems among parents with intellectual disabilities: the buffering role of resources. (4th December 2014) - Meppelder, M.; Hodes, M.; Kef, S.; Schuengel, C.
Abstract Background Parents with intellectual disabilities (ID) are at risk for high levels of parenting stress. The present study evaluated resources, including parental adaptive functioning, financial resources and access to a support network, as moderators of the association between child behaviour problems and parenting stress. Method A total of 134 parents with ID and their children (ages 1–7 years) were recruited from 10 Dutch care organisations. Questionnaires were administered to the parents to obtain information on parenting stress in the parent and child domain, financial resources and their support network. Teachers and care workers reported on child behaviour problems and parental adaptive functioning, respectively. Results Parents experienced more stress with regard to their children than towards their own functioning and situation. Parenting stress was less in parents who were not experiencing financial hardship. Child behaviour problems were associated with high child‐related parenting stress, not parent‐related parenting stress. Large support networks decreased the association between child behaviour problems and child‐related parenting stress. Financial resources did not significantly moderate the association. Conclusions Parenting stress among parents with ID is focused on problems with the child, especially when little social support is available.